Development of synthetic methods of Azaheterocycles via Vinylic substitutions and an aerobic oxidation of allylic alcohols catalysed by N-Hydroxyindoles - Shen, Shusu (2013)
More and more new synthetic methodologies have been developed and widely applied in organic synthesis. Two major synthetic methods were developed during my PhD course: part I is synthesis of azaheterocycles based on nucleophilic vinylic substitution reaction and part II is the selective aerobic oxidation of allylic and benzylic alcohols catalyzed by N-hydroxyindoles and copper(I) chloride. Unlike the well known nucleophilic substitution at an sp3 carbon, the nucleophilic substitution at an sp2 carbon was considered as an unfavorable process. However, some successful examples have been established in our group recently. As a synthetic application of the intramolecular concerted nucleophilic substitution at an sp2 carbon of vinylic halides, the intramolecular cyclization of vinyl bromides with intramolecular thioamide or thiourea moieties were studied for the synthesis of five-membered heterocycles. In Chapter 2.1 and 2.2 was described the preparation of various five-membered heterocycles, including 2,5-disubstituted thiazoles 36 and 1,3,4-trisubstituted imidazole-2-thiones 56 (Scheme 1). The formation of six-membered ring 78 is discussed in Chapter 2.4 (Scheme 2), but it was found that the intramolecular vinylic nucleophilic substitution mechanism was not the only mechanism, two other pathways were also proposed for this transformation. Envisioning that N-hydroxyindole may act as a precursor of nitroxyl radicals and/or oxoammonium species, we synthesized a series of substituted N-hydroxyindoles. It was found that tert-butyl 1-hydroxy-2-methyl-6-(trifluoromethyl)-1H-indole-3-carboxylate (NHI-1), which can be easily prepared in high yield, acts as an efficient catalyst for highly chemoselective aerobic oxidation of alcohols with the combined use of copper(I) chloride. A variety of primary and secondary allylic and benzylic alcohols were oxidized into the corresponding α,β-unsaturated carbonyl compounds in good yields without affecting non-allylic alcohols (Scheme 3). Furthermore, such a catalyst system exhibits a considerable stereoselectivity in the oxidation of stereoisomers of cyclic allylic alcohols, where the equatorial alcohols are oxidized in preference to to the corresponding axial ones. After some mechanistic studies, this aerobic oxidation was found to be catalyzed by the nitroxyl radical of NHI-1 as the real active species.